Implementing Culturally Responsive Teaching to Improve Students Engagement and Comprehension in Learning Recount Texts - Siahaan, Agnes Rosalyn; Lis Supiatman; Nazla Rakhmi Lubis (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This classroom action research aimed to investigate the effectiveness of implementing Culturally Responsive Teaching (CRT) to improve student engagement and comprehension in learning recount texts. The study was conducted with 36 tenth-grade students at SMA Negeri 3 Kisaran during the 2024/2025 academic year. Using the Kemmis and McTaggart (1988) model, the research was carried out in two cycles comprising planning, action, observation, and reflection phases. Data were collected through student engagement questionnaires, comprehension tests, observation sheets, and documentation. The results showed significant improvements: student engagement increased from 52.5% in the pre-cycle to 91% in Cycle II, and the percentage of students achieving the minimum passing score rose from 30% to 92%. Observations and documentation confirmed increased participation, motivation, and writing quality. The findings indicate that CRT is an effective pedagogical approach for enhancing engagement and academic achievement by making learning more culturally relevant and inclusive.